Doses de máxima eficiência física e econômica de flor-de-seda no rendimento de caupi-hortaliça - Vieira, Flaviana de Andrade (Universidade Federal Rural do Semi-Árido, 2014)
Cowpea-vegetable (Vigna unguiculata (L.) Walp) is a grain legume, used in the human food, largely grown in semi-arid areas of the Brazilian Northeast. Green manure is an economical form and alternative for the low-income farmers to fertilize their crops. However, there is no information about the use of this green manure using roostertree. In view of this, this study aimed to determine the dose of agroeconomic efficiency maximum of roostertree in the green grain yield of cowpea-vegetable and its production components in function of different amounts of roostertree incorporated into the soil in sole crop. The experiment was conducted at the Experimental Farm Rafael Fernandes, from August to November 2013. The experimental design was a randomized complete block design with 5 replications. The treatments consisted of the following amounts of roostertree biomass incorporated into the soil: 20, 35, 50 and 65 t ha-1 on a dry basis. Each experimental plot had a total area of 3.6 m2 (3.00 m x 1.20 m), with a harvest area of 2.00 m2, containing 40 plants of cowpea-vegetable spaced of 0.50 m between rows with 10 plants per linear meter. The cultivar of cowpea-vegetable planted was BRS Itaim. It was incorporated 30% of the roostertree on August 22, 2013 in all plots, 20 days before planting. During the time of decomposition were performed daily irrigations in two shifts, one in the morning and one in the evening. After 20 days of sowing was made the incorporation of the 70% remaining of the material between the lines of the plots. The characteristics evaluated were: number of green pods per square meter, number of green grains per pod, yield of green pods, weight of 100 green grains and dry mass of grains and green pods. The economic indicators determined were: gross income (GI), net income (NI), production cost (PC), rate of return (RR) and profit margin (PM). The doses for maximum agronomic and economic efficiency of cowpea-vegetable were obtained with the incorporation into the soil of the quantities of roostertree of 59.4 and 54 t ha-1, respectively, with the yield of green grains of 3.25 t ha-1 and net income of R $ 9,624.74
Doses of physical and economic efficiency maximum of roostertree in the cowpea-vegetable yield
Keywords: Green manure; Calotropis procera; Vigna unguilata; Adubação verde; Calotropis procera; Vigna unguilata; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA